Urgent problems of jury trial functioning in the Republic of Kazakhstan - Kozhakhmetov, G.Z.; Rakhimgulova, M.B. (KSU Publ., 2017)
The institute of jurors is one of the important institutes of protective legal proceedings, however it is not given due consideration. The jury trial does not have historical traditions in the Republic of Kazakhstan as it has recently been introduced. Nevertheless, presently the jury trial is directed to its further independence and is an important guarantee against the repressive prosecution. This article investigates the problems of necessity and functioning of the jury trial in the Republic of Kazakhstan and the questions of number of jurors. The article also considers the legal proceedings with participation of jury members under the Criminal Procedure Code of the Republic of Kazakhstan. The legislation and court practice in this sphere has been analyzed, the ways to solve the problems have been proposed in the article.
Қазақстан Республикасы алқаби соты қалыптасуының заманауи мəселелері
Актуальные проблемы функционирования суда присяжных в Республике Казахстан
Keywords: jury; judicial system; jurisdiction of cases; jurors; selection of candidates; the Criminal Procedure Code of the Republic of Kazakhstan; court session; defendant; competitiveness of the parties; legal culture